Is changing status through housing tenure associated with changes in mental health? Results from the British Household Panel Survey. Issue 1 (7th October 2014) - Popham, Frank; Williamson, Lee; Whitley, Elise
Abstract : Background: Actual or perceived status, such as housing tenure, may impact on health through stress-inducing social comparisons. Studies of how status change impacts mental health change are rare but important because they are less prone to confounding. Methods: We used data from the British Household Panel Survey to compare psychological distress in local authority renters who opted to buy their home under the UK's Right to Buy (RTB) policy versus those who continued to rent the same (social non-mover (SNM)) or a different (social mover (SM)) local authority property or who bought privately (owner mover (OM)). General Health Questionnaire (GHQ-12) scores before and after any change in tenure and/or address were compared across groups using a difference-in-difference approach. Results: Individuals who moved house (bought or rented) were younger while those who bought (the same or different house) were better off, more likely to be employed, and had higher educational qualifications. Individuals who bought their home (under RTB or privately) had lower distress scores from the outset. Individuals who moved house (bought or rented) experienced a rise in distress prior to moving that was no longer evident 1 year after the move. There was no evidence that changing tenure reduced psychological distress comparing (difference (95% CI)) average GHQ score 2 years preaddress and 1 year postaddress/tenure change in RTB vs SNM, SM, OM: −0.08 (−0.68 to 0.51), 0.16 (−0.70 to 1.01) and −0.17 (−1.28 to 0.94), respectively). Conclusions: Changing tenure under RTB did not, on average, impact psychological distress, suggesting that this status change did not change mental health.